2018
DOI: 10.1002/jts.22322
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy for Co‐Occurring Posttraumatic Stress Disorder and Alcohol Use Disorders in Veterans: Pilot Treatment Outcomes

Abstract: Posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) frequently co‐occur and are associated with worse outcomes together than either disorder alone. A lack of consensus regarding recommendations for treating PTSD–AUD exists, and treatment dropout is a persistent problem. Acceptance and Commitment Therapy (ACT), a transdiagnostic, mindfulness‐ and acceptance‐based form of behavior therapy, has potential as a treatment option for PTSD–AUD. In this uncontrolled pilot study, we examined ACT for PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 25 publications
4
51
0
1
Order By: Relevance
“…Two studies have shown ACT as an effective therapy for alcohol use disorder. Meyer et al in 2018 carried out an uncontrolled pilot study of 43 veterans with post-traumatic stress disorder (PTSD) [28]. At the end of 10 to 12 sessions of ACT with TAU, the veterans demonstrated a significant reduction in the total number of drinks and heavy drinking days [28].…”
Section: The Use Of Act In the Treatment Of Single Substance Abusementioning
confidence: 99%
See 4 more Smart Citations
“…Two studies have shown ACT as an effective therapy for alcohol use disorder. Meyer et al in 2018 carried out an uncontrolled pilot study of 43 veterans with post-traumatic stress disorder (PTSD) [28]. At the end of 10 to 12 sessions of ACT with TAU, the veterans demonstrated a significant reduction in the total number of drinks and heavy drinking days [28].…”
Section: The Use Of Act In the Treatment Of Single Substance Abusementioning
confidence: 99%
“…Meyer et al in 2018 carried out an uncontrolled pilot study of 43 veterans with post-traumatic stress disorder (PTSD) [28]. At the end of 10 to 12 sessions of ACT with TAU, the veterans demonstrated a significant reduction in the total number of drinks and heavy drinking days [28]. Ehman and Gross in 2018 also conducted a case study on a 29-year-old woman who was a college student and had AUD.…”
Section: The Use Of Act In the Treatment Of Single Substance Abusementioning
confidence: 99%
See 3 more Smart Citations